2020
DOI: 10.1088/1757-899x/910/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Cost perspective for sustainability in Industrialised Building System (IBS) projects

Abstract: Since 1998, the Construction Development Industry Berhad (CIDB) has been long promoting Industrialised Building System (IBS) in Malaysia. However, the use of IBS has not achieved an impressive number which only 10% and 50% have widely used in the past said CIDB in 2006. This research study focused on why IBS practice is still in an unconvincing market state of use and how sustainability in its cost perspective influences the use of IBS in each project. A questionnaire has been developed consists of four sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…4,5 However, due to the poor compatibility between different elastomers, improving the interfacial compatibility between polar and non-polar rubbers has been a research hotspot. 6 Styrene-butadiene rubber (SBR) and nitrile rubber (NBR) are the most commonly used non-polar and polar synthetic rubbers, respectively. [6][7][8][9][10] SBR has excellent mechanical strength, mechanical properties, aging resistance and wear resistance, and is widely used in various fields such as tyres, hoses, and medical instruments, with excellent comprehensive properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 However, due to the poor compatibility between different elastomers, improving the interfacial compatibility between polar and non-polar rubbers has been a research hotspot. 6 Styrene-butadiene rubber (SBR) and nitrile rubber (NBR) are the most commonly used non-polar and polar synthetic rubbers, respectively. [6][7][8][9][10] SBR has excellent mechanical strength, mechanical properties, aging resistance and wear resistance, and is widely used in various fields such as tyres, hoses, and medical instruments, with excellent comprehensive properties.…”
Section: Introductionmentioning
confidence: 99%
“…6 Styrene-butadiene rubber (SBR) and nitrile rubber (NBR) are the most commonly used non-polar and polar synthetic rubbers, respectively. [6][7][8][9][10] SBR has excellent mechanical strength, mechanical properties, aging resistance and wear resistance, and is widely used in various fields such as tyres, hoses, and medical instruments, with excellent comprehensive properties. [11][12][13] However, the styrene-butadiene rubber contain no polar groups, but contains rigid benzene rings, which leads to an increase in the distance between the molecular chains, thus making it easy for solvent oil to destroy the three-dimensional cross-linked network after vulcanization.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that costs are heavily impacted by a wide variety of variables, from the time of project estimation until the time of project completion. Studies by the previous studies [10][11][12][13], and others have found the elements that significantly influence construction costs in different nations. They argue that these aspects have a direct bearing on the construction organizations' responsibilities for managing the cost, socio-cultural, economic, external, technological, and political settings in which they operate, all of which have an impact on the construction costs.…”
Section: Introductionmentioning
confidence: 99%